A Journey of Difference: The Voices of Women Leaders - Showunmi, Victoria (Frontiers in Education, 2021)
A journey of difference; the voices of women leaders. Author: Dr Victoria Showunmi UCL Institute of Education Contact details: v.showunmi@ioe.ac.uk UCL IOE 20 Bedford Way, London WCL This paper offers a view on narrative inquiries based upon leadership, in order to shed light on women’s of colour and multicultural groups experience and nuance understanding of their leadership career path. Since black and other ethnic group women are ‘theoretically erased’ (Crenshaw, 1989: 139), this empirical study offers an insight into how gender, class and race influence on women’s leadership practices in three countries, while it adds to theorising identity and leadership at schools in different international contexts. This paper intends to give voice to women leaders who are making a difference in their organisation. During the past decade, interest in gender and leadership has grown to the extent that it is slowly becoming part of the leadership norm. Narrative inquiries are treated as a means of a systematic data gathering and analysis which challenges the traditional views of gender discussions (thus gender is predominantly about white women) and incorporating ethnic minority around leadership. Unfolding the stories of women –from multi-ethnic groups and mixed social class- higher education leadership positions in England, and Pakistan, may expose differences of interpretations offered by researchers from a racially and ethnically diverse background (black and white Europeans). Hence, an issue that arises is whether researchers’ cultural background affects data interpretation of studies with a highly qualitative stance.